Organic carbon storage change in China's urban landfills from 1978–2014 - Shidong Ge; Shuqing Zhao (Environmental Research Letters, 2017)
China has produced increasingly large quantities of waste associated with its accelerated urbanization and economic development and deposited these wastes into landfills, potentially sequestering carbon. However, the magnitude of the carbon storage in China’s urban landfills and its spatial and temporal change remain unclear. Here, we estimate the total amount of organic carbon (OC) stored in China's urban landfills between 1978 and 2014 using a first order organic matter decomposition model and data compiled from literature review and statistical yearbooks. Our results show that total OC stored in China’s urban landfills increased nearly 68-fold from the 1970s to the 2010s, and reached 225.2–264.5 Tg C (95% confidence interval, hereafter) in 2014. Construction waste was the largest OC pool (128.4–157.5 Tg C) in 2014, followed by household waste (67.7–83.8 Tg C), and sewage sludge was the least (19.7–34.1 Tg C). Carbon stored in urban landfills accounts for more than 10% of the country’s carbon stocks in urban ecosystems. The annual increase (i.e. sequestration rate) of OC in urban landfills in the 2010s (25.1 ± 4.3 Tg C yr ^−1 , mean ± 2SD, hereafter) is equivalent to 1% of China's carbon emissions from fossil fuel combustion and cement production during the same period, but represents about 9% of the total terrestrial carbon sequestration in the country. Our study clearly indicates that OC dynamics in landfills should not be neglected in regional to national carbon cycle studies as landfills not only account for a substantial part of the carbon stored in urban ecosystems but also have a respectable contribution to national carbon sequestration.